2017
DOI: 10.1111/ijn.12524
|View full text |Cite
|
Sign up to set email alerts
|

The use of educational video to promote maternal self‐efficacy in preventing early childhood diarrhoea

Abstract: Diarrhoea is responsible for high rates of infant morbidity and mortality. It is multifactorial, manifested by socioeconomic, hygienic, and maternal factors. The aim of this study is to evaluate the effects of an educational video on maternal self-efficacy for the prevention of childhood diarrhoea. This was a randomized trial conducted in the state of Ceará, Brazil. Participants were 2 groups (comparison and intervention), composed of mothers of children under 5 years of age. Group membership was allocated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
12

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 30 publications
2
14
0
12
Order By: Relevance
“…Results of previous researches, which served as a basis for elaborating the survey on the primary care for promoting maternal self-efficacy in preventing childhood diarrhea, showed that mothers presented similar characteristics to those from this study, such as low education and families consisting of more than three members (7,12) . These aspects reflect the reality of part of the Brazilian population, so that the educational primer emerges as a valid and reliable material both for economically disadvantaged families and those with greater socioeconomic conditions, since the primer is understandable to the lowest stratum of the population, it will also be for the highest.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Results of previous researches, which served as a basis for elaborating the survey on the primary care for promoting maternal self-efficacy in preventing childhood diarrhea, showed that mothers presented similar characteristics to those from this study, such as low education and families consisting of more than three members (7,12) . These aspects reflect the reality of part of the Brazilian population, so that the educational primer emerges as a valid and reliable material both for economically disadvantaged families and those with greater socioeconomic conditions, since the primer is understandable to the lowest stratum of the population, it will also be for the highest.…”
Section: Discussionsupporting
confidence: 66%
“…Thus, it is appropriate to point out that the lack of knowledge, difficulty to memorize and the vulnerability of the customers can be some of the factors justifying the development of educational technologies (31) , being important that the textual preparation of educational materials be suitable for the educational and cultural level of the target audience (32) . Such requirements have been met by other researchers, whose experimental studies showed that the application of an educational video (7) and a TV series (33) , built from the theory of self-efficacy and validated by judges of content and the target population, favored the elevation of maternal self-efficacy in preventing childhood diarrhea and in breastfeeding, contributing to reducing diarrhea in children, in addition to increasing the period of exclusive breastfeeding, respectively (7,33) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(4) The need for prevention strategies is highlighted, aimed at families of children under five years of age, which can improve knowledge and maternal confidence in preventive care for childhood diarrhea. (5) Thus, an educational video based on Bandura's Theory of Self-Efficacy titled "Childhood Diarrhea: you can prevent it", applied to mothers of children under five years old, permitted enhancing maternal self-efficacy to prevent childhood diarrhea and reducing the cases of diarrhea up to two months after this intervention. After this period, however, the mothers' self-efficacy decreased, suggesting the need to develop and use other technologies in this area to keep up the implementation of interventions to prevent this condition.…”
Section: Introductionmentioning
confidence: 99%
“…In a randomized controlled clinical trial that sought the effects of an educational video on maternal self-efficacy in preventing childhood diarrhea, it was shown that video had a significant effect on maternal self-efficacy, demonstrating the efficacy of using this type of technology (35) .…”
Section: Use Of Soft Technologies and Educational Practices To Prevenmentioning
confidence: 99%